FABRICATION METHOD OF FRP BASED HIGH PRESSURE MEMBRANE HOUSING - Khoiruddin
Membrane technology has an important role in the separation process. Several advantages offered by the membrane-based separation technologies such as ease of scale up because it’s modularity. Another advantages are the low energy requirement and environmental friendly because no chemical addition required. Water treatment and natural gas are the most dominant membrane-based separation processes Membrane process in seawater desalination and separation of CO2 fromnatural gas require high operating pressures. So it needs a special housing that can be operated at high pressure. Metal is a suitable material for this application because it has excellent mechanical strength. However, the major disadvantage of metal are low corrosion resistance and large density. FRP (fiber reinforced polymer) based composite materials is a potential alternative for this application. The advantages of composite materials over metal are (1) beter corrosion resistance, (2) the specific mechanical properties (per unit weight of the mechanical properties of the material) is much higher than metal because of lower density and (3) the ease of the fabrication process The aim of this research are to study the effect of fabrication parameter and polymer matrix to mechanical properties of FRP based membrane housing produced. The fabrication parameter investigated are fiber orientation (30o , 55o , and 80o ) and fiber volume fraction (53,33% - 80%). Polymer matrix used are unsaturated polyester and epoxy Experimental result shows that fiber orientation and polymer matrix type significantly affect burst pressure value. On the other hand, the effect of fiber volume fraction on burst pressure value is insignificant. Burst pressure value of membrane housing is increase with the increase of winding angle until 55o then decrease drastically in winding angle of 80o . This behaviour is observed in both epoxy matrix and unsaturated polyester matrix. The level of shrinkage is small and difference between eposy matrix and unsaturated polyester is insignificant.